2a-9=6a+7

Simple and best practice solution for 2a-9=6a+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2a-9=6a+7 equation:


Simplifying
2a + -9 = 6a + 7

Reorder the terms:
-9 + 2a = 6a + 7

Reorder the terms:
-9 + 2a = 7 + 6a

Solving
-9 + 2a = 7 + 6a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6a' to each side of the equation.
-9 + 2a + -6a = 7 + 6a + -6a

Combine like terms: 2a + -6a = -4a
-9 + -4a = 7 + 6a + -6a

Combine like terms: 6a + -6a = 0
-9 + -4a = 7 + 0
-9 + -4a = 7

Add '9' to each side of the equation.
-9 + 9 + -4a = 7 + 9

Combine like terms: -9 + 9 = 0
0 + -4a = 7 + 9
-4a = 7 + 9

Combine like terms: 7 + 9 = 16
-4a = 16

Divide each side by '-4'.
a = -4

Simplifying
a = -4

See similar equations:

| v=1/3*12*13 | | x(y/y-x)^2 | | v=1/3*12*13 | | 7x+10=-4 | | 0.25(6+8)= | | 7x+10=-4 | | (-4x^3)=(-5x^7) | | (-4x^3)=(-5x^7) | | 0.5x=0.5x+1 | | 63=7(10-x) | | 4x+6x=15+5 | | -7m+20=#17m-10 | | 4(6+2i)=24+8i | | -4/12 | | 58+5x+10+11x+2=180 | | (7+i)+13=7+(i+13) | | 0.25(6x+8)= | | -3(1+4.5)=-17.5 | | 7p+16=-26 | | (4+i)+(-4-i)=0 | | 14xy-21xy^2= | | 3x+25y=15 | | 3-2(4x+5)=3-8x+10 | | 8(3t+2)-60=60 | | 3x-25y=15 | | -4(2/-2)^2= | | -3(y+7)=56 | | -34m=6m-4 | | 6a+3=0 | | -4(2/-2)^2 | | 6-2*7= | | 14m-21= |

Equations solver categories